Thesaurus Construction Project for the Persian Manuscripts - Elaheh Rohidel; DR.Nahid Banieghbal (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2008)
Purpose: Manuscripts as written works of past generations are important collections in research and university libraries in Iran. They convey useful information about different subject areas. The need to this enormous amount of information emphasis on their organization and the application of the new electronic information technologies. Methodology: Regarding to the presence of more than 5,000 special vocabularies in the field of manuscript, it is essential to control and organize the terms according to their subject limitations in a systematic design. Since, thesaurus is one of the controlling tools of words and information terms in this subject then preparing an electronic comprehensive thesaurus in addition to published version is recommended. Therefore, a plan for thesaurus and its structure and the limitation of codicology terms is surveyed. Finding: The result of survey for the first time in Iran is a structure suggested for the thesaurus of codicology according to available samples and a brief example of thesaurus has been rendered.